New data on the development of the Baradla Cave (Hungary, Aggtelek karst) - Márton, Veress (Acta Carsologica, 2012)
The development of karst landforms of the Aggtelek Plateau was investigated concerning the role of these valleys in the genesis of the Baradla Cave, which is located on the Plateau. New data were collected by geophysical method (Vertical Electrical Sounding) from a few dolines of a selected valley of the Aggtelek Plateau. The geophysical profiles confirm that the dolines of the valley bottom did not develop from sinkholes, but they are solution dolines. Morphological characteristics of the valleys of the Plateau suggest that these valleys are not the continuation of the valley of the recent covered karst. The former catchment area of these valleys might have been on the Plateau and north of Kecső valley. Their bottoms tilted into southern direction. Therefore the subsurface capture places of their streams might have been near to the recent sinking line.The sediments (Borsodi Gravel Formation) which were eroded from the above mentioned areas also contributed to the genesis of the Baradla Cave.